2022
DOI: 10.1038/s41598-022-25261-8
|View full text |Cite
|
Sign up to set email alerts
|

The maize Ga1-s allele confers protection against ga1 pollen in popcorn and dent corn

Abstract: Because corn pollen can be carried great distances by wind, maintaining genetic purity of corn grain is challenging. The challenge is substantially reduced in popcorn, which carries the Ga1-s allele preventing pollination by ga1 plants, which include the vast majority of non-popcorn commercial maize varieties in the U.S.. Ga1-s can be transferred into dent corn but the effectiveness of the Ga1-s allele in popcorn and dent corn has never been compared, which is important because each are regulated differently r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(10 reference statements)
1
0
0
Order By: Relevance
“…The quantity of yellow kernels on white lines was around 5%, so the process of MABB in this case was unsuccessful. The most likely explanation of our results, consistent with Lauter et al (2022), could be the presence of modifier genes that increase or decrease the effectiveness of pollen exclusion or that, alternatively, modifiers were lost during the backcrossing. These authors also concluded that converting dent corn varieties to Ga1-S requires careful testing for their ability to exclude pollen.…”
Section: Resultssupporting
confidence: 79%
“…The quantity of yellow kernels on white lines was around 5%, so the process of MABB in this case was unsuccessful. The most likely explanation of our results, consistent with Lauter et al (2022), could be the presence of modifier genes that increase or decrease the effectiveness of pollen exclusion or that, alternatively, modifiers were lost during the backcrossing. These authors also concluded that converting dent corn varieties to Ga1-S requires careful testing for their ability to exclude pollen.…”
Section: Resultssupporting
confidence: 79%